2020
DOI: 10.1021/acsaem.0c01156
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Improvement of Thermoelectric Figure-of-Merit in SnTe through In Situ-Created Te Nanoinclusions

Abstract: SnTe exhibits very low Seebeck coefficient along with high electrical–thermal conductivities owing to very high hole concentration that results from intrinsic Sn vacancies. All these unfavorable thermoelectric parameters restrict pristine SnTe from becoming an outstanding thermoelectric material. In this work, we demonstrate the improvement in figure-of-merit of SnTe through in situ creation of Te nanoinclusions in the SnTe matrix. We have intentionally added excess Te in stoichiometric Sn/Te (1:1) for the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The EDS spectra of all the compositions of La-doped SnTe, Sn SnTe. 21 The composition Sn 0.92 La 0.08 Te shows the presence of grain boundaries, nanoprecipitates of La due to the solubility limit and defects although Fig 4(c) represents that all the three compositions of La-doped SnTe exhibit defects of various length scales and grain boundaries. These grain boundaries along with the defects present in the sample contribute to phonon scattering and thus lattice thermal conductivity is reduced.…”
Section: Results Andmentioning
confidence: 98%
See 2 more Smart Citations
“…The EDS spectra of all the compositions of La-doped SnTe, Sn SnTe. 21 The composition Sn 0.92 La 0.08 Te shows the presence of grain boundaries, nanoprecipitates of La due to the solubility limit and defects although Fig 4(c) represents that all the three compositions of La-doped SnTe exhibit defects of various length scales and grain boundaries. These grain boundaries along with the defects present in the sample contribute to phonon scattering and thus lattice thermal conductivity is reduced.…”
Section: Results Andmentioning
confidence: 98%
“…The uniqueness of the planes is that they are the most active planes for the slip to occur and arises due to the anisotropic growth of the sample. 21 The study by Yang et al 36 reported that these kink bands serve as scattering centres for the phonons and thus suppress the thermal conductivity (Fig. 3(d)).…”
Section: Results Andmentioning
confidence: 98%
See 1 more Smart Citation
“…There are various approaches to increase the ZT value of materials. These are alloying, [83][84][85][86][87] PGEC, 24,25,88 band engineering, [89][90][91] and nanostructuring, [92][93][94][95] which are discussed below.…”
Section: Strategies For Enhancement Of Ztmentioning
confidence: 99%
“…[165][166][167] For instance, GaAs nanoinclusions dispersed in n-type Bi 2 Te 2.7 Se 0.3 lead to reduced thermal conductivity while maintaining a large power factor. 168 Ahmad et al 93 achieved a high ZT of 1.5 at 750 K owing to reduced lattice thermal conductivity due to hierarchical scattering of phonons and an improved Seebeck coefficient via energy filtering for Te nanoinclusions created in-situ in SnTe. Kong et al 169 introduced nano-TiO 2 particles in the Cu 2 Te matrix in order to reduce the thermal conductivity.…”
Section: Nanoinclusions In the Matrixmentioning
confidence: 99%